Enhancing Young Learners’ English Skills Through Game-Based Pedagogy - Sulastri Sulastri; Arismunandar Arismunandar; Nurhikmah H; Ratnawati Ratnawati (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of this study is to find out whether or not game- based pedagogy was effective in increasing students’ interest, active participation, enthusiasm and sympathy of the elementary school in learning English at SD Pemulung Rappokalling assumed that the learning media and methods provided by the teacher were still less attractive so students were not interested, unenthusiastic and unindependent in finishing the assignments. This study took one of the inhibiting factors of learning carried out in the class to increase interest in learning. The subjects of this study were 20 students of fifth grade students of SD Pemulung Rappokalling. The type of this research used Kemmis and Taggart models carried out 2 cycles, each of consisting of planning, action, observation and reflection stages in each cycle. The data in this study was obtained from the observation checklist written by the collaborator and observer. Methods of collecting data was obtained through observation, interviews and documentation. This research used a research methodology known as the classroom action research approach, data was analyzed since the learning action was implemented and developed during the learning process to conclude whether the use of the game -based pedagoy was effective in increasing students' interest in learning English. The results of this study indicated that learning English by applying the game -based pedagoy could improve the mastery of vocabulary and interest of students, this could be proven in the improvement of the percentage of the pre -cycle was obtained at 49.25%, cycle I was 61.38% and the second cycle reached 76%.